2016
DOI: 10.18576/jpac/020203
|View full text |Cite
|
Sign up to set email alerts
|

Metal Complexes of Acetone Thiosemicarbazone: Synthesis, Spectral Characterization and Pharmacological Studies

Abstract: Acetone thiosemicarbazone (ACTSC) a very versatile Schiff base ligand reacted with some transition metals forming coordination complexes. These solid complexes have been isolated and characterized on the basis of elemental analysis and spectroscopic studies (UV-Vis, FT-IR and 1 H-NMR). The infrared spectra of the complexes revealed bands at (736-864 nm) and (1608-1627 nm) attributed to (>C=S) and (>C=N) respectively. These bands experienced a negative shift when compared to the spectral of the parent ligand. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Consequently, testis exposed to higher dosage of the herb could have reduced sperm output. These findings share similarities with previous works reporting histopathological disruptions or distortions of the seminiferous tubules and certain male fertility parameters [17,18]. In contrast however, Sutyarso and Kanedi, [19] reported that fruit extract of black pepper had positive effects on male fertility, particularly sperm count and seminiferous tubule integrity.…”
Section: Seminiferous Tubules Integritysupporting
confidence: 90%
“…Consequently, testis exposed to higher dosage of the herb could have reduced sperm output. These findings share similarities with previous works reporting histopathological disruptions or distortions of the seminiferous tubules and certain male fertility parameters [17,18]. In contrast however, Sutyarso and Kanedi, [19] reported that fruit extract of black pepper had positive effects on male fertility, particularly sperm count and seminiferous tubule integrity.…”
Section: Seminiferous Tubules Integritysupporting
confidence: 90%
“…Anticancer activities of thiosemicarbazones were reported by various authors over worldwide [8][9][10][11][12][13] . Because of having various applications, in recent years a large number of authors reported the synthesis and characterization studies of different thiosemicarbazone ligands [14][15][16][17][18] . The importance of thiosemicarbazones both in analytical and biological fields owe to us to synthesize new thiosemicarbazones.…”
Section: Introductionmentioning
confidence: 99%